Are PD-1 inhibitors effective for recurrent/metastatic nasopharyngeal carcinoma? Meta-analysis and systematic review - Yan, Le; Ren, Bi; Hu, Rongqiu; Zhang, Huiping; Gou, Haocheng (Frontiers in Pharmacology, 2023)
Objective: For metastatic/recurrent nasopharyngeal carcinoma (NPC) patients, a programmed cell death protein 1 (PD-1) is a controversial option. This meta-analysis aimed to investigate the efficacy and safety of PD-1 inhibitors in patients with metastatic/recurrent NPC. Methods: Electronic databases such as PubMed, Embase, Cochrane library, and Web of Science were manually searched until 1 July 2022, and Stata 15.0 was used to analyze the data. Result: A total of 10 studies were included, of which three were randomized controlled trials with data, and seven were single-arm studies. For randomized controlled trial (RCT) study, ORR [OR = 1.11, 95% CI (.49, 2.52); p = .812], OS [1-year OR = 1.26, 95% CI (.76, 2.08); p = .367], [2-year OR = 1.04, 95% CI (.39, 2.71); p = .928] in patients with metastatic/recurrent NPC were consistent with PD-1 inhibitor therapy and conventional chemotherapy. However, PD-1 inhibitor had higher 1-year PFS than conventional chemotherapy [OR = 2.16, 95% CI (1.26, 3.70); p = .005]. For single-arm studies, after PD-1 inhibitor therapy, the ORR of patients with recurrent/metastatic NPC reached [ES = 37%, 95 CI (17%–56%)], 1-year OS [ES = 61%, 95% CI (46%–76%)], 2-year [ES = 16%, 95% CI (6%–26%)], and 1-year PFS [ES = 16%,95% CI (12%–20%)]. Conclusion: The efficacy of PD-1 inhibitor monotherapy in patients with metastatic/recurrent nasopharyngeal carcinoma was not significantly different from that of conventional chemotherapy; however, due to the limitations of the included studies, further phase III RCTs are required to corroborate our conclusion. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022342400; Identifier: CRD42022342400.